Health education with dietary adherence for people with diabetes mellitus in the community - Indra Tri Astuti; Ching Min Chen (Jurnal Edukasi Ilmiah Kesehatan, 2025)
Introduction: Dietary adherence remains a critical challenge for individuals with diabetes mellitus (DM), especially within community settings where lifestyle factors strongly influence disease control. Health education plays an crucil role in enhancing self-management behaviors and improving glycemic outcomes. This study aimed to evaluate the effect of structured health education on dietary adherence among people with DM in the community. Methods: A quasi-experimental pre–post design was conducted among 120 participants with type 2 DM in a community health program. Participants received four weekly sessions of health education focusing on nutrition knowledge, meal planning, and behavioral motivation, delivered through interactive workshops and visual aids. Data were collected using the Diabetes Self-Management Questionnaire (DSMQ) and a 24-hour dietary recall, and analyzed using paired t-tests and multiple regression to assess changes in adherence and identify influencing factors. Results: Post-intervention findings showed a significant improvement in dietary adherence scores (p < 0.001) and a mean reduction in fasting blood glucose levels (p < 0.05). Education level, social support, and perceived self-efficacy were strong predictors of adherence improvement (R² = 0.48). Participants reported enhanced understanding of carbohydrate control and portion management. Conclusion: Community-based health education effectively improves dietary adherence and metabolic outcomes in people with DM. Integrating culturally relevant education and continuous community engagement is crucial to sustaining behavioral changes. This approach supports primary prevention efforts and strengthens community health systems in diabetes management